OPINIONS OF PRESCHOOL TEACHERS AND COUNSELLORS ON THE IMPORTANCE OF GUIDANCE SERVICES IN PRESCHOOL - N. Bulbul; D. Çelik (Trakia Journal of Sciences, 2024)
Preschool education is a very important educational stage in the development of the child. Guidance services in pre-school education have an important place due to the characteristics of the developmental period children are in. The aim of the guidance services to be provided in this period can be listed as the child's self-knowledge and acceptance, socialisation, ensuring adaptation to school, enabling the child to discover his/her interests and abilities, developing problem-solving skills, identifying children with special educational needs, determining the child's readiness for transition to basic education and providing guidance to families. This study, which aims to evaluate preschool guidance services according to the views of preschool teachers and guidance counsellors, was designed in accordance with the phenomenological model, one of the qualitative research methods. The participant group of the research will consist of preschool teachers and guidance counsellors working in primary schools and independent kindergartens in Edirne Central District. The data of the research will be collected with a semi-structured interview form prepared by the researchers and analysed by descriptive analysis. The findings of the research will be discussed in line with the related literature.